Pelatihan Dasar Microsoft word dan Bahasa Inggris untuk Meningkatkan Keterampilan Siswa Kelas IV SD Negeri Kaliputih - Nabila, Zulfa; Asroriyah, Atik Muhimatun; Mitsalina, Endah; Heriyanto, Dwi; Malihah, Kuni Zakiyatul; Subahtiar, Desta; Surtinah, Surtinah; Jagad, Jundan Maulahaq Sapu; Indrianingsih, Citra; Budi, Agus Setia; Salasa, Sandi; Sari, Fenita; Nawangsih, Nawangsih; Soimah, Umi Riyadotus (Abdibaraya, 2024)
In the current digital era, mastering information technology and foreign language skills is very important to prepare the younger generation to face challenges throughout the world, but at SDN Kaliputih there are no special subjects and there are only extracurriculars about information and communication technology (ICT). Meanwhile, English subjects are only given to grades one and four. Based on the problems faced by SD N Kaliputih, UMNU Kebumen students and lecturers held basic training activities on the use of Ms.Office which focused on Microsoft Word and English for class IV students. This training was attended by 23 students consisting of men and women. This activity aims to see the impact of basic Microsoft Word and English training on improving the skills of class IV students at Kaliputih State Elementary School. Activities are carried out using qualitative descriptive methods and direct practice. From the results of the activities we carried out we got results: students mastered the various menus or displays provided by Microsoft Word and were able to operate them well. For the English training itself, the students seemed to enjoy and be more confident in speaking English vocabulary than before. This training is very useful for elementary school students to increase insight and knowledge about the Microsoft Word application and increase English vocabulary, so that students are able to hone their skills by following developments in digital technology and correct English pronunciation.